"Discours sur le mot" et "discours du mot": la dialectique perplexe du signe et de l'objet. L'exemple du mot castillan sacre. (Signifiances (Signifying), 2017)
I will call discourse about the word the available hypotheses on the etymology, the history and the recognized meanings of a word : such hypotheses are codified in lexicographic literature. I will call discourse of the word the meaning that is uttered by its sound substance and its morphologic structure. As will be exemplified by the word sacre, this discourse of the word depends to a large extent on the system of the language to which it is linked by the various discourses about the word. Both the discourse of the word and the discourse about the word contribute to build up a puzzled dialectical relationship between the sign and the object in a double direction of the meaning which moves from the object to the sign uttered in the language, and from the sign to the object multiplied by the representations that the form of the sign conveys.